2017
DOI: 10.1525/elementa.216
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of reactive gases and methane variability in the coastal boundary layer of the central Mediterranean basin

Abstract: We present a characterization of reactive gases (RG: O 3 , NO, NO 2 , SO 2 , CO) and methane (CH 4 ) variability in the central Mediterranean basin, analyzing in situ measurements at three new permanent WMO/GAW Observatories in Southern Italy: Capo Granitola -CGR (Sicily), Lamezia Terme -LMT (Calabria) and Lecce -ECO (Apulia). At all the measurement sites, a combination of the breeze wind system (especially at CGR and LMT), PBL dynamics, anthropogenic/natural emissions, and photochemistry lead the appearance o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 52 publications
2
13
0
Order By: Relevance
“…Seasonal behavior shows higher values during the cold season and minimum during the warmer period, due to the lower atmospheric lifetime (Gilge et al, 2010;Schultz et al, 2015). This result agrees with observations reported by Cristofanelli et al (2017), who showed similar seasonal cycle for other location in southern Italy.…”
Section: Gas-phase Pollutantssupporting
confidence: 91%
“…Seasonal behavior shows higher values during the cold season and minimum during the warmer period, due to the lower atmospheric lifetime (Gilge et al, 2010;Schultz et al, 2015). This result agrees with observations reported by Cristofanelli et al (2017), who showed similar seasonal cycle for other location in southern Italy.…”
Section: Gas-phase Pollutantssupporting
confidence: 91%
“…In Capo Granitola, the major prevailing wind directions during the campaign were between WNW-NW to N-NE, which was a peculiar wind distribution (generally NW and SE) at this site [25], with winds from inland generally associated with higher concentrations and more polluted events. Associated with the N-NE wind direction, the OC and EC concentrations were higher than average (43-59%), while the carbonaceous concentrations associated with wind from the (W-NW) direction were observed to be lower (65-71%), in both size fractions.…”
Section: Influence Of Meteorological Parameters On Measured Concentramentioning
confidence: 80%
“…The area experiences some pollution coming from the transport sector (airport, cruises from/to Gioia Tauro and local traffic mainly for E-NE direction), houses, and agriculture. More details on the site can be found in Cristofanelli et al [25]. Capo Granitola Observatory (CGR, 37.6° N 12.6° E; 5 m a.s.l.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The CGR location is affected by the sea-land breeze regime, with prevailing gentle wind breezes (on average 3 ± 1 m/s) from inland (NW-NE) during the night and prevailing winds from the sea (W-SE) ( Figure 1b) during daytime [36]. The average temperature ranged, through the daily cycle, between 8.8 °C and 26.6 °C, while relative humidity between 24% and 91% during the investigation period.…”
Section: Introductionmentioning
confidence: 99%